Application of Food-Grade Enzymes, Bacteriocins And Probiotics as Biological Food Preservatives - K, Monisha (Technoarete Transactions on Recent Research in Applied Microbiology and Biotechnology, 2022)
The demand of the consumers tends to be artificial additive-free, long foods of shelf-life, nutritious, ready-to-eat foods. The significance of the natural and food preservatives compounds is totally increased for the excessive use of the preservative compounds in the food rather than the synthetic compounds. The bacteriocins combine with the several modes of hurdle approach that can enhance the effects of the preservatives and reduce the resistance of the antimicrobial. The probiotic products enhance the health agents because they regulate inflammation inside the gastronomical tract, and it also has the functional effects that are immune. The bacteriocins are the antimicrobial compounds and they are considered biological preservatives or natural preservatives. These are having bacteriostatic effects and it shows the spectrum of the antimicrobial activity that is against the bacterial strains. The bacteriocins unlike the antibiotics are more specific and they can kill the pathogens by not causing any detrimental imbalances for hosting the microbiota. The safety of the Lb. plantarum runs through several beneficial claims in order to understand the related features of the probiotic. The effect of the usage of probiotics and essential oil is much lesser than that when used combined. This study is focused on the natural preservatives of the food grade enzymes, the main application of the bacteriocin in biological food preservatives and the use of the probiotics in the food preservatives. Keyword :Lb. Plantarum, E. coli, Listeria, T. polium, Lactobacillus casei